Wolf in the Folklore of Croats - Dragić, Marko (Poznańskie Studia Slawistyczne, 2012)
The paper focuses on the significant role of wolf in the Croatian folklore that has been confirmed by a series of analyses over the thirty contemporary original field records. The socalled wolf processions were still performed in many places of the country just before the Homeland War in 1991. Often described in a word vukavarski, the processions were always initiated by an act of killing the wolf since the animal was traditionally assumed as a symbol of evil and subsequently as a cause of severe damage. In order to celebrate such an act, the wolf killer, accompanied by a small group of hunters, had to march through the village. The group was obliged to sing or recite spells, derived from an apotropaic rite, in front of the country houses. As for the hosts, they were satisfied to receive the procession (such a satisfaction was usually expressed by different rewards) since all the neighborhood had got rid off another dangerous animal.